Orbital Rashba effect in a surface-oxidized Cu film - Go, Dongwook; Jo, Daegeun; Gao, Tenghua; Ando, Kazuya; Bluegel, Stefan; Lee, Hyun-Woo; Mokrousov, Yuriy (Physical Review B, 2021)
Recent experimental observation of an unexpectedly large current-induced spin-orbit torque in surface oxidized Cu on top of a ferromagnet pointed to a possibly prominent role of the orbital Rashba effect (ORE) in this system. Here, we use first principles methods to investigate the ORE in a system of oxygen monolayer deposited on top of a Cu(111) film. We show that surface oxidization of the Cu film leads to a gigantic enhancement of the ORE near the Fermi energy. The resulting chiral orbital texture in the momentum space is exceptionally strong, reaching as much as ∼0.5L in magnitude. We find that resonant hybridization between O p states and Cu d states is responsible for the emergence of the ORE at the interface. We also present a minimal model that captures the emergence of the ORE through the pd hybridization mechanism. We demonstrate that an application of an external electric field to the system generates colossal orbital Hall currents which are an order of magnitude larger than the spin Hall currents found in heavy metals. This implies that the "orbital torque"mechanism may be significant in surface oxidized Cu/ferromagnet structures. Our results encourage an experimental verification of the rich orbital physics in surface oxidized Cu films through optical measurements such as angle-resolved photoemission spectroscopy and momentum microscopy.
CRIS-Team Scopus Importer:2023-03-27